Leitliniengerechte stationäre psychiatrisch-psychotherapeutische Behandlung der Zwangsstörung: Normative Personalbedarfsermittlung = Guideline-adherent inpatient psychiatric psychotherapeutic treatment of obsessive-compulsive disorder : normative definition of personnel requirements - Klein, Jan Philipp; Herpertz, Sabine (Der Nervenarzt, 2016)
BackgroundGuideline-oriented inpatient psychiatric and psychotherapeutic treatment of patients with obsessive-compulsive disorder (OCD) is an important part of the care available for these patients. It may not be adequately reflected in the current personnel resources available according to the German psychiatry personnel regulation (Psych-PV).ObjectivesThe goal of this work was to assess the personnel resources necessary for a guideline-oriented inpatient psychiatric and psychotherapeutic treatment of patients with OCD and compare the necessary resources with the resources available according to Psych-PV.MethodsBased on the German national guidelines for OCD and a meta-analysis on treatment intensity, we formulated a normative weekly treatment plan. Based on this plan we calculated the necessary personnel resources and compared these with the resources available according to Psych-PV category A1 (standard care).ResultsThe weekly treatment time for a guideline-oriented inpatient psychiatric and psychotherapeutic treatment of patients with OCD is 23.5 h per week. This corresponds to a weekly personnel requirement of 20.9 h. This requirement is only partly reflected in the Psych-PV (17.3 h, 82.8 %). The coverage of personnel resources by Psych-PV is even lower for psychotherapy provided by psychiatrist and psychologists (38.3 %, i. e. 183 min in the normative plan versus 70 min in Psych-PV).ConclusionsThe current paper shows that the personal resources required for a guideline-oriented inpatient psychiatric and psychotherapeutic treatment of patients with OCD is not adequately reflected in the German psychiatry personnel regulation (Psych-PV). The actual shortage may be underestimated in our paper.
Gesehen am 06.02.2019